The Comparative Effect of Citrullus colocynthis Hydro-Alcoholic Extract and Metformin on Morphometric Ovarian Follicles Disorders in Estradilol valerate-Iinduced Polycystic Ovary Syndrome Rats - Barzegar Bafrouei, Mohammad Hossein; Khazali, Homayoun; Kalantar, Seyyed Mehdi; Khoradmehr, Arezoo (Galen Medical Journal, 2018)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder that affects 6-10% of women in reproductive age. The medicinal values of Citrullus colocynthis extract (CCT) stems from its anti-oxidative and anti-inflammatory effects. This study evaluated the comparative effect of CCT and metformin on morphometric ovarian disorders in PCOS rats. Materials and Methods: Fifty female Wistar rats having 2-3 consecutive estrous cycles during two weeks were divided into five groups (n=10 each group). The rats in the control group only received sesame oil as estradiol valerate solvent, whereas the rats in the sham group were injected intramuscularly with 4 mg/rat estradiol valerate-induced PCOS. Following PCOS induction, the rats in the metformin group received 50 mg/kg metformin orally for three weeks. Rats in the Extract group were treated with 50 mg/kg plant extract for 21 days following the induction with PCOS. Additionally, the rats in metformin+ extract group were treated with the combination of 50 mg metformin plus plant extract for three weeks. The ovaries were removed and were fixed for tissue processing. The slices were stained by hematoxylin-eosin after clearing and hydration. Follicular count and morphometric changes were evaluated in primordial, primary, pre-antral and antral follicles. Results: The mean diameter of primordial follicle was similar in all groups, but mean diameter of primary follicle decreased in the sham group (145.50± 49.26 µm) compared to metformin (278.76± 156.64 µm), extract (311.70± 147.74 µm) and metformin+ extract groups (265.35± 88.16 µm). The diameter of pre-antral and antral follicles in the sham group were significantly larger than those in the control group, but were not significantly different in all other groups including metformin, extract, and metformin+ extract in comparison with control group (P< 0.05). Conclusion: In this study, the data has demonstrated that CCT like metformin could improve follicular morphometric disorders in PCOS rats. [GMJ.2018;7:e1045]